An In Situ High‐Energy Synchrotron X‐Ray Diffraction Study of Directional Solidification in Binary TiAl Alloys. Issue 11 (3rd May 2021) - Oehring, Michael; Matthiessen, Dirk; Blankenburg, Malte; Schell, Norbert; Pyczak, Florian
Abstract : Phase formation and microstructure selection during solidification in γ‐TiAl alloys are highly relevant, both with respect to the microstructure and texture of cast alloys and to directional solidification, which allows to obtain a unique combination of properties. However, during cooling to room temperature, the solidifying phases transform to low‐temperature phases, which mask the prior situation during solidification. A new inductive crucible‐free zone melting furnace is used in this work, which is specially designed for in situ investigations of solidification using synchrotron radiation. Herein, alloys with 45 and 48 at% Al are studied, and it can be shown that with varying withdrawal rate, a change from α solidification to synchronous β + α solidification occurs in Ti–48Al, as it is predicted in the literature. Furthermore, it is observed that by increasing the withdrawal rate, a preferred <001> growth of the β phase occurs in alloys with 45 at% Al, which is interpreted as a transition to dendritic solidification. The observations are compared with a microstructure selection map calculated according to the nucleation and constitutional undercooling (NCU) model proposed in the literature. Abstract : A new inductive crucible‐free zone melting furnace is used for in situ investigations of solidification of binary TiAl alloys by synchrotron radiation. With increasing withdrawal rate, a change from α solidification to synchronous β + α solidification occurs in Ti–48Al, whereas in Ti–45Al, a transition from planar to dendritic growth of the β phase is observed.